1983
DOI: 10.1111/j.1540-6261.1983.tb03629.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Capital Structure Change on Firm Value: Some Estimates

Abstract: This study develops a model based on current corporate finance theories which explains stock returns associated with the announcement of issuer exchange offers. The major independent variables are changes in leverage multiplied by senior security claims outstanding and changes in debt tax shields. Parameter estimates are statistically significant and consistent in sign and relative magnitude with model predictions. Overall, 55 percent of the variance in stock announcement period returns is explained. The evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(56 citation statements)
references
References 19 publications
1
53
2
Order By: Relevance
“…Even after that study, no strong research work had been carried out to identify evidence of a relation between a firm's value and the size of its debt tax shield, evidence of a relation between a firm's value and the size of its debt tax shield. Further, Masulis (1983) found that both stock prices and firm values are positively related to changes in debt level and leverage; security prices are negatively related to these capital structure change variables. This evidence is consistent with models of optimal capital structure and with the hypothesis that debt level changes release information about changes in firm value.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Even after that study, no strong research work had been carried out to identify evidence of a relation between a firm's value and the size of its debt tax shield, evidence of a relation between a firm's value and the size of its debt tax shield. Further, Masulis (1983) found that both stock prices and firm values are positively related to changes in debt level and leverage; security prices are negatively related to these capital structure change variables. This evidence is consistent with models of optimal capital structure and with the hypothesis that debt level changes release information about changes in firm value.…”
Section: Literature Reviewmentioning
confidence: 97%
“…None of these studies of capital structure changes, however, resolves the issue of what factors determine the negative average stock price response. Nor do they completely explain the motivation for these capital structure changes As stated by Masulis (1983) presented an extensive theoretical literature available with respect to the optimal capital structure. However, evidence of a relation between changes in capital structure and firm value are seldom reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Take the stock price and relationship of financial operation as the research topic, the stock price of corporation rose with the level of financial leverage discovered by Masulis (1983). Simultaneously, the value of corporation is related to the debt level positively.…”
Section: Financial Performancementioning
confidence: 99%
“…Despite various capital structure theories that have tried to rationalise the impact of leverage, past literature often provides mixed empirical evidence on the role of leverage in return predictability. Among some well-known studies, Hamada (1972), Masulis (1983), and Bhandari (1988) in early years found that stock returns are positively associated with leverage. Fama and French (1992), as well as Strong and Xu (1997), later discover the negative relationship between book leverage and returns, but the relationship becomes insignificant when book-to-market is considered.…”
Section: Introductionmentioning
confidence: 99%